Behavioural factors affecting foreign exchange futures traders: irrationality, overconfidence and bias - Loh, Kang Hern (2020)
In this paper, the main objectives of our study are (1) To investigate the trading behaviour of different traders: speculators, hedgers and small traders in the context of the currency futures market, and (2) To determine whether traders are motivated by irrationality and bias within the context of foreign exchange futures market. Based on the theory of dispersion of belief, different traders should differ in terms of motive and informativeness, resulting in different trading behaviours. Different trading behaviour often lead to behavioural bias as well as irrational behaviour. To examine these, our research will examine how these different traders react to both return and volatility information across 6 foreign exchange futures market.